2013
DOI: 10.1007/s11481-013-9495-z
|View full text |Cite
|
Sign up to set email alerts
|

Potential Roles of Microglial Cell Progranulin in HIV-Associated CNS Pathologies and Neurocognitive Impairment

Abstract: Progranulin (PGRN) is a highly unusual molecule with both neuronal and microglial expression with two seemingly unrelated functions, i.e., as a neuronal growth factor and a modulator of neuroinflammation. Haploinsufficiency due to loss of function mutations lead to a fatal presenile dementing illness (frontotemporal lobar degeneration), indicating that adequate expression of PGRN is essential for successful aging. PGRN might be a particularly relevant factor in the pathogenesis of HIV encephalitis (HIVE) and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 91 publications
1
11
0
Order By: Relevance
“…We and others previously described an increase in the microglial‐derived protein sTREM2 in the CSF of both ADAD and late‐onset AD patients (Heslegrave et al , ; Piccio et al , ; Suárez‐Calvet et al , ,b). Since CSF PGRN also gradually increases during the course of the disease and it is mainly produced by activated microglia (Daniel et al , ; Naphade et al , ; Petkau et al , ; Philips et al , ; Kleinberger et al , ; Suh et al , ), we investigated whether these two proteins are associated (Figs A and B, and A–C). In a linear regression model, we found that CSF PGRN and CSF sTREM2 were significantly associated in ADAD mutation carriers of the DIAN study (β = +0.514, P < 0.0001, Fig B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We and others previously described an increase in the microglial‐derived protein sTREM2 in the CSF of both ADAD and late‐onset AD patients (Heslegrave et al , ; Piccio et al , ; Suárez‐Calvet et al , ,b). Since CSF PGRN also gradually increases during the course of the disease and it is mainly produced by activated microglia (Daniel et al , ; Naphade et al , ; Petkau et al , ; Philips et al , ; Kleinberger et al , ; Suh et al , ), we investigated whether these two proteins are associated (Figs A and B, and A–C). In a linear regression model, we found that CSF PGRN and CSF sTREM2 were significantly associated in ADAD mutation carriers of the DIAN study (β = +0.514, P < 0.0001, Fig B).…”
Section: Resultsmentioning
confidence: 99%
“…Together with the fact that CSF PGRN considerably overlaps between groups, these results show that, consistent with previous data ( CSF PGRN is associated with CSF sTREM2 and markers of neurodegeneration in both autosomal dominant and late-onset Alzheimer's disease We and others previously described an increase in the microglialderived protein sTREM2 in the CSF of both ADAD and late-onset AD patients (Heslegrave et al, 2016;Piccio et al, 2016;Suárez-Calvet et al, 2016a,b). Since CSF PGRN also gradually increases during the course of the disease and it is mainly produced by activated microglia (Daniel et al, 2000;Naphade et al, 2010;Petkau et al, 2010;Philips et al, 2010;Kleinberger et al, 2013;Suh et al, 2014), we investigated whether these two proteins are associated (Figs 6A and B, and 7A-C). In a linear regression model, we found that CSF PGRN and CSF sTREM2 were significantly associated in ADAD mutation carriers of the DIAN study (b = +0.514, P < 0.0001, Fig 6B).…”
Section: Csf Pgrn Is Not a Clinical Diagnostic Biomarker For Admentioning
confidence: 99%
See 1 more Smart Citation
“…al. on the paradoxical roles of progranulin (PGRN) in modulating antiviral immunity as well as neuronal dysfunction in the context of HIV infection further emphasizes the dual roles of neuronal growth factors (Suh et al, 2013). These authors propose CSF PGRN as a candidate surrogate marker of HAND.…”
Section: Growth Factor Mimetics and Antagonists As Therapeuticsmentioning
confidence: 99%
“…While neurons constitutively express PGRN, microglial cells are the primary source of regulatable PGRN in the brain [27][29]. Analysis of PGRN expression in systemic organs also demonstrated that tissue macrophages are the main expressors of PGRN with certain epithelial cells also expressing PGRN but at much lower levels [30][33]. PGRN expression in the two cell types is also differently regulated.…”
Section: Introductionmentioning
confidence: 99%